2013
DOI: 10.1093/carcin/bgt067
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor   expression induces changes in the microRNA pool in human colon cancer cells

Abstract: There is epidemiological, animal and in vitro evidence that estrogen receptor β (ERβ) can mediate protective effects against colon cancer, but the mechanism is not completely understood. Previous research has indicated critical pathways whereby ERβ acts in an antitumorigenic fashion. In this study, we investigate ERβ's impact on the microRNA (miRNA) pool in colon cancer cells using large-scale genomic approaches, bioinformatics and focused functional studies. We detect and confirm 27 miRNAs to be significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 83 publications
5
40
0
1
Order By: Relevance
“…In support of our study showing the tumor suppressor role of ERβ, there are emerging evidences showing that ERβ has an anti-oncogenic role in the development and progression of some tumor types, including ovarian cancer, renal cell carcinoma, prostate cancer, and colon cancers. [23][24][25][26][27][28][29] Our study and these previous reports altogether indicated a protective role of ERβ in the development and progression of cancer.…”
supporting
confidence: 56%
“…In support of our study showing the tumor suppressor role of ERβ, there are emerging evidences showing that ERβ has an anti-oncogenic role in the development and progression of some tumor types, including ovarian cancer, renal cell carcinoma, prostate cancer, and colon cancers. [23][24][25][26][27][28][29] Our study and these previous reports altogether indicated a protective role of ERβ in the development and progression of cancer.…”
supporting
confidence: 56%
“…Additionally, non-genomic effects via phosphorylation and regulation of enzymes that impact cell physiology, such as kinases and phosphatases, and activity through the membrane-bound G protein-coupled estrogen receptor 1 (GPR30/GPER1), have been described [36]. While ERα protein is not detected in the colonic epithelium or in CRC (http://www.proteinatlas.org/ENSG00000091831-ESR1/tissue/colon), ERβ has been confirmed as the predominant form of ER in a number of studies [3745]. …”
Section: Estrogen Receptor Beta (Erβ) Has a Role In Crcmentioning
confidence: 99%
“…From the phenotype of ERb K/K mice, ERb in the colon appears to decrease proliferation and increase apoptosis, suggesting a tumor suppressive and tumor preventive effect (Wada-Hiraike et al 2006). ERb has also been shown to change the micro RNA pool in human colorectal cancer cells (Edvardsson et al 2013) and to regulate miR-135b and mismatch repair gene expressions in colorectal cells (He et al 2012).…”
Section: Colonmentioning
confidence: 99%